Effectiveness of Restitution Implementation in Restoring the Rights of Child Victims of Sexual Violence in Semarang City - Cahyowati, Yeti; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The issue of the vagueness of the restitution regulation for child victims of sexual violence has resulted in the violation of the rights and justice for child victims of sexual violence. This thesis aims toto know and analyze the effectiveness of the implementation of restitution for child victims of sexual violence in Semarang City at this time and to know and analyze the obstacles and solutions in the implementation of restitution for child victims of sexual violence in Semarang City at this time. The type of approach used is the sociological legal method where law in this study is conceptualized as ideas, culture, and views of society regarding legal regulations implemented in the social environment of society. Based on the research conducted, it is known that the implementation of protection and recovery of child victims of sexual violence has not been effective, this is indicated by the still minimal implementation of restitution for child victims of sexual violence which ultimately also hinders the implementation of rehabilitation for child victims of sexual violence. The obstacles that influence are the constraints of legal regulations that still do not explicitly and clearly contain the implementation of restitution, this culturally also hinders the system of implementing restitution for child victims of sexual violence. The solutions that can be done are Efforts in the Implementation of Counseling, Improving Facilities and Infrastructure in Efforts to Prevent and Eradicating Sexual Harassment Against Children, the Need for a Protection House for Child Victims of Sexual Harassment During the Legal Process, Providing Understanding to Victims Regarding Their Rights, and Need to regulate the amount of restitution for child victims of sexual violence.